ANALISIS KETERAMPILAN BERTANYA SISWA PADA PEMBELAJARAN IPA MATERI SUHU DAN KALOR DENGAN MODEL PROBLEM BASED LEARNING DI SMP NEGERI 2 JEMBER - Dewi Ika Pratiwi; Nur Wandiyah Kamilasari; Dama Nuri; Supeno Supeno (FKIP Universitas Jember, 2019)
Abstract: The knowledge has always starts with asking. For teachers, asking questions is seen as an activity to encourage, guide, and assess students' thinking abilities. For students, asking questions is an important part of exploring information, informing what is known, and directing what is not yet known. The aim of this research is to determine the quantity and quality of students' asking ability based on revised Bloom's taxonomy by applying the problem based learning model to the material temperature and heat. The method in this research is descriptive qualitative method. This research was conducted at SMP Negeri 2 Jember with research respondents being all students of class VII F of the odd semester of the 2019/2020 school year. Data collection using observation sheets to ask students. Based on the data obtained, it shown that the quantity of students who ask questions is 37.63%. The quality of questions in this research is 100% in the low level but there are no questions classified as high level. Based on these results, it can be concluded that the asking ability of students of class VII F in SMP Negeri 2 Jember are relatively low and need to be improved. Keywords: question skills, problem-based learning, natural science.